2015
DOI: 10.1590/2317-1545v37n3150086
|View full text |Cite
|
Sign up to set email alerts
|

Physiological quality of soybean seeds produced in four edaphoclimatic regions of Santa Catarina

Abstract: -The production of soybeans in the state of Santa Catarina is quite significant in the national context, since the state is recognized for producing seeds with high standards of physiological quality, due to the use of modern technologies and favorable climatic conditions. The aim of this study was to evaluate the physiological quality of soybean seeds produced by major companies in the state of Santa Catarina, analyzed in three seasons: harvesting (reception at UBS), after processing and at the time of sale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(8 reference statements)
0
2
0
1
Order By: Relevance
“…Furthermore, the effect of the environment over quality expression is also constantly verified in literature (Gomes et al, 2012;de Pádua et al, 2014;Frandoloso et al, 2015). The interaction T x L, for the test of the mass of one thousand grain, indicated that the responses regarding environmental variations were not coincident for the evaluated cultivars.…”
Section: When Analyzing Interactions T X L and L X Ymentioning
confidence: 68%
“…Furthermore, the effect of the environment over quality expression is also constantly verified in literature (Gomes et al, 2012;de Pádua et al, 2014;Frandoloso et al, 2015). The interaction T x L, for the test of the mass of one thousand grain, indicated that the responses regarding environmental variations were not coincident for the evaluated cultivars.…”
Section: When Analyzing Interactions T X L and L X Ymentioning
confidence: 68%
“…In studies carried out with the objective of evaluating the physiological quality of soybean seeds produced by companies from different regions of the state, values similar to those found in the present study were observed. In the 2013/2014 crop, Frandoloso, Meneghello, André, Deuner and Menegaz (2015), evaluating the physiological quality of 24 batches produced in the municipalities of Xanxerê, Abelardo Luz, Campos Novos and Canoinhas, obtained a mean of 88% germination and 85% vigor.…”
Section: Resultsmentioning
confidence: 99%
“…A primeira contagem de germinação (Tabela 1) foi realizada aos cinco dias após a semeadura e foi como um indicativo do vigor das sementes, pois sementes mais vigorosas germinam mais rápido NAKAGAWA, 2000). As porcentagens de plântulas normais tanto em V9 (78,7%) quanto em R1 (78,4%) são consideradas baixas, pois vários autores têm encontrado porcentagens de plântulas normais na primeira contagem acima de 90% para sementes de soja com alto vigor (WENDT et al, 2014;FRANDOLOSO et al, 2015).…”
Section: Resultsunclassified